Preeclampsia and Blood Pressure Trajectory during Pregnancy in Relation to Vitamin D Status - Bärebring, Linnea; Bullarbo, Maria; Glantz, Anna; Leu Agelii, Monica; Jagner, Åse; Ellis, Joy; Hulthén, Lena; Schoenmakers, Inez; Augustin, Hanna (PLOS ONE, 2016)
Every tenth pregnancy is affected by hypertension, one of the most common complications and leading causes of maternal death worldwide. Hypertensive disorders in pregnancy include pregnancy-induced hypertension and preeclampsia. The pathophysiology of the development of hypertension in pregnancy is unknown, but studies suggest an association with vitamin D status, measured as 25-hydroxyvitamin D (25(OH)D). The aim of this study was to investigate the association between gestational 25(OH)D concentration and preeclampsia, pregnancy-induced hypertension and blood pressure trajectory. This cohort study included 2000 women. Blood was collected at the first (T1) and third (T3) trimester (mean gestational weeks 10.8 and 33.4). Blood pressure at gestational weeks 10, 25, 32 and 37 as well as symptoms of preeclampsia and pregnancy-induced hypertension were retrieved from medical records. Serum 25(OH)D concentrations (LC-MS/MS) in T1 was not significantly associated with preeclampsia. However, both 25(OH)D in T3 and change in 25(OH)D from T1 to T3 were significantly and negatively associated with preeclampsia. Women with a change in 25(OH)D concentration of ≥30 nmol/L had an odds ratio of 0.22 (p = 0.002) for preeclampsia. T1 25(OH)D was positively related to T1 systolic (β = 0.03, p = 0.022) and T1 diastolic blood pressure (β = 0.02, p = 0.016), and to systolic (β = 0.02, p = 0.02) blood pressure trajectory during pregnancy, in adjusted analyses. There was no association between 25(OH)D and pregnancy-induced hypertension in adjusted analysis. In conclusion, an increase in 25(OH)D concentration during pregnancy of at least 30 nmol/L, regardless of vitamin D status in T1, was associated with a lower odds ratio for preeclampsia. Vitamin D status was significantly and positively associated with T1 blood pressure and gestational systolic blood pressure trajectory but not with pregnancy-induced hypertension.